2018
DOI: 10.1108/rpj-09-2016-0154
|View full text |Cite
|
Sign up to set email alerts
|

A review of 3D concrete printing systems and materials properties: current status and future research prospects

Abstract: Purpose -Three-dimensional printing of concrete (3DPC) has a potential for the rapid industrialization of the housing sector, with benefits of reduced construction time due to no formwork requirement, ease of construction of complex geometries, potential high construction quality and reduced waste. Required materials adaption for 3DPC is within reach, as concrete materials technology has reached the point where performancebased specification is possible by specialists. This paper aims to present an overview of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(106 citation statements)
references
References 33 publications
0
89
0
Order By: Relevance
“…A study conducted using this type of concrete has been found to have favorable characteristics and therefore satisfies the requirements of most structural applications [61]. This type of concrete has been reinforced with steel; however, other fibers, such as glass or carbon fibers, can also be used for reinforcement [25].…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…A study conducted using this type of concrete has been found to have favorable characteristics and therefore satisfies the requirements of most structural applications [61]. This type of concrete has been reinforced with steel; however, other fibers, such as glass or carbon fibers, can also be used for reinforcement [25].…”
Section: Methodsmentioning
confidence: 97%
“…Reinforcement remains one of the challenges of 3D printing in construction. One method of reinforcement of 3D-printed structures is placing the reinforcing steel bars manually between the layers before or during printing [25]. However, this method is challenging since the steel rebar creates an obstacle for the movement of the printer head.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The downside of 3D-printed construction is the lack of codes and standards regulating the industry-existing design and construction standards are not applicable to 3D printing methods [15]. However, the importance of codes and standards tends to diminish in remote, isolated, or expeditionary environments due to the need to build structures as expediently as possible, thus, this is likely not a serious concern.…”
Section: Structural Designmentioning
confidence: 99%